(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The study investigated the gut content and recorded morphometric and hematological parameters in the Eurasian collared dove (Streptopelia decaocto). Materials and Methods: 24 samples of healthy birds (12 from each sex) were collected from different wetlands in Punjab, Pakistan, from December 2022 until February 2023. Birds were captured live for blood samples, morphometric, and gut analyses. Results: The current study revealed that mensural measurements showed no significant differences in all parameters except tail length, which was significantly longer in males (14.59 ± 0.30) compared to females (12.88 ± 0.43). Hematological parameters were hemoglobin, 23.95 gm/dl; red blood cells, 3.97 × 106/µl; white blood cells, 429.9.67 × 103/µl; hematocrit, 72.14%; mean corpuscular volume, 183.24 FL; mean corpuscular hemoglobin, 61.70 pg; mean corpuscular hemoglobin concentration, 32.37 pg; platelets, 7.01/µl; and red cell distribution width, 110.86/µl. The percentages of neutrophils, lymphocytes, monocytes, and eosinophils were 71.33%, 23.03%, 3.30%, and 1.43%, respectively. The gut content of the Eurasian collared dove mainly consisted of rice, wheat, corn, and millet seeds. Some stony materials were also present. Conclusion: Our study concluded that male and female Eurasian collared doves are alike in biometrics (except tail length) and hematological profiles. Gut content and weight were also similar. Males were slightly larger than females. The gut content showed that the Eurasian collared dove mainly feeds on rice, wheat, corn, and millet seeds. In this study, hematological parameters were also studied. J. Adv. Vet. Anim. Res., 10(2): 244–248, June 2023 http://doi.org/10.5455/javar.2023.j675